2020
DOI: 10.3390/pr8081004
|View full text |Cite
|
Sign up to set email alerts
|

Methods Used for the Compaction and Molding of Ceramic Matrix Composites Reinforced with Carbon Nanotubes

Abstract: Ceramic matrix composites reinforced with carbon nanotubes are becoming increasingly popular in industry due to their astonishing mechanical properties and taking into account the fact that advanced production technologies make carbon nanotubes increasingly affordable. In the present paper, the most convenient contemporary methods used for the compaction of molding masses composed of either technical ceramics or ceramic matrix composites reinforced with carbon nanotubes are surveyed. This stage that precedes d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 202 publications
(203 reference statements)
0
4
0
Order By: Relevance
“…Injection molding is a common process for the shaping of thermoplastics [ 1 , 2 , 3 ], thermoplastic elastomers [ 4 , 5 , 6 ], composites [ 7 , 8 , 9 ], as well as metals [ 10 , 11 , 12 ] and ceramics [ 13 , 14 ]. The central concept around the method is the melting and plasticization of the material and feeding it into a mold cavity, where the material is solidified by cooling [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Injection molding is a common process for the shaping of thermoplastics [ 1 , 2 , 3 ], thermoplastic elastomers [ 4 , 5 , 6 ], composites [ 7 , 8 , 9 ], as well as metals [ 10 , 11 , 12 ] and ceramics [ 13 , 14 ]. The central concept around the method is the melting and plasticization of the material and feeding it into a mold cavity, where the material is solidified by cooling [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, on the other hand, the high hardness and brittleness of ceramic materials also make it difficult for shaping and machining. Methods such as slurry casting, dry pressing, and plastic molding have certain disadvantages [8][9][10][11]: forming complex components requires the use of molds with high geometric accuracy. Because high-precision molds are costly to manufacture and have long production runs, it is difficult to continuously improve and upgrade the product; sintered samples often require either laser processing or machining using diamond cutting tools to ensure sufficient accuracy in the dimensions and shape of the finished product; some special shapes and elements are difficult to produce using conventional molding processes, such as internal cavities, holes, and internal grooves.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the compressibility of air, Figures 8 and 9 show that when the compressor speed increased, the forming pressure increased faster at the same time; in contrast, this trend was not apparent for the hydraulic forming process. This indicated that the hydraulic moulding method had better ability to control the forming pressure [40,41].…”
Section: Figure 13mentioning
confidence: 91%